Penerapan Sistem Keamanan Web Menggunakan Metode Web Aplication Firewall - Riska, Riska; Alamsyah, Hendri (UNIB Press, 2021)
The application of a security system on the web needs to be done considering that the web itself can be accessed through a public network. In this study, a Web Application Firewall (WAF)-based security system will be implemented using modsecurity, in which the purpose of implementing this web security system is to understand the concept of a security system on the web and pay attention to the results before the application of the firewall and after the application of the firewall on the web. This research uses experimental research methods, in this study the implementation of a web application firewall (WAF) using modsecurity as a web security system is carried out, then an analysis is carried out to get the right recommendations for a firewall as a web security system. The results of this study indicate that a firewall using the modSecurity module and rule based on the Web Application Firewall (WAF) on a web security system can block SQL Injection, Cross Site Scripting (XSS), and Command Execution by displaying an error message to the user who performs the command.